2020
DOI: 10.14379/iodp.proc.372b375.203.2020
|View full text |Cite|
|
Sign up to set email alerts
|

Data report: reconnaissance of bulk sediment composition and clay mineral assemblages: inputs to the Hikurangi subduction system

Abstract: Introduction 2 Methods 5 Results 15 Conclusions 16 Acknowledgments 16 References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Specifically, marls and chalk were found at 510–849 mbsf, and the lower portion of the sediment package (below 849 mbsf) consists of a volcaniclastic facies (Figure 2). The latter material contains basalt clasts, a clay‐rich (primarily saponite) altered matrix and zeolite cementation and, for a few tens of meters, carbonate‐rich cementation (Figure 2; Barnes et al., 2019; Underwood, 2020). Data from seismic reflection surveys (e.g., Bell et al., 2014) and regional drilling (Barnes et al., 2020) point to a plate interface which is likely patchy due to the heterogeneous incoming protolith containing regionally variable thicknesses of the carbonate and volcaniclastic sediments.…”
Section: The Hikurangi Sses and Iodp Expeditions 372/375mentioning
confidence: 99%
“…Specifically, marls and chalk were found at 510–849 mbsf, and the lower portion of the sediment package (below 849 mbsf) consists of a volcaniclastic facies (Figure 2). The latter material contains basalt clasts, a clay‐rich (primarily saponite) altered matrix and zeolite cementation and, for a few tens of meters, carbonate‐rich cementation (Figure 2; Barnes et al., 2019; Underwood, 2020). Data from seismic reflection surveys (e.g., Bell et al., 2014) and regional drilling (Barnes et al., 2020) point to a plate interface which is likely patchy due to the heterogeneous incoming protolith containing regionally variable thicknesses of the carbonate and volcaniclastic sediments.…”
Section: The Hikurangi Sses and Iodp Expeditions 372/375mentioning
confidence: 99%
“…Estimates for the composition of the Unit IV pelagic sequence are obtained from Barnes et al (2019) and are based on their reported mineral abundances (∼50% calcite, 30% clay, and 10% each quartz and feldspar; see Figure F5 in that article). Clay mineralogy is further separated based on powdered XRD analyses from Underwood (2020), and consists of ∼52% smectite, 37% illite, and 11% chlorite + kaolinite. The mineral abundances and idealized formulas for these minerals were used to estimate composition of the Unit IV pelagic sequence (Figure 3, Table 1).…”
Section: Compositional Estimatesmentioning
confidence: 99%
“…Details about the data-collection methods can be found in Blum (1997) and the expedition reports (e.g., Harris et al, 2013;Henry et al, 2012;Jaeger et al, 2014;McNeill et al, 2017;Saito et al, 2010;Wallace et al, 2019). Additional XRD data, including information on the clay minerals, were obtained from published studies (Ikari et al, 2013(Ikari et al, , 2018Rosenberger et al, 2020;Screaton et al, 2017;Steurer & Underwood, 2003;Underwood, 2020;Underwood & Guo, 2013). As all analyses were not conducted on the same discrete samples, we identified the nearest neighbor measurements (always within 5 meters) on samples from the same lithologic unit and lithology.…”
Section: Shipboard Measurementsmentioning
confidence: 99%
“…This is not unexpected; ash in contact with seawater reacts to form hydrous clay minerals. In the case of samples from Hikurangi and Sunda, smectite is the dominant clay mineral (Rosenberger et al, 2020;Underwood, 2020). Smectite clays contain abundant interlayer water, accounting for up to 25% of the bulk mass (Brown & Ransom, 1996).…”
Section: High Velocity Clustermentioning
confidence: 99%